2020
DOI: 10.1101/2020.05.11.088112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for strong mutation bias towards, and selection against, T/U content in SARS-CoV2: implications for attenuated vaccine design

Abstract: Large-scale re-engineering of synonymous sites is a promising strategy to generate attenuated viruses for vaccines. Attenuation typically relies on de-optimisation of codon pairs and maximization of CpG dinculeotide frequencies. So as to formulate evolutionarily-informed attenuation strategies, that aim to force nucleotide usage against the estimated direction favoured by selection, here we examine available whole-genome sequences of SARS-CoV2 to infer patterns of mutation and selection on synonymous sites. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…As identified by previous studies [30][31][32][33][34][35], we recover evidence of strong mutational biases across the SARS-CoV-2 genome. A remarkably high proportion of CàU changes was observed relative to other types of SNPs and this pattern was observed at both non-homoplasic and homoplasic sites ( Figures S6-S8).…”
Section: Distribution Of Recurrent Mutationssupporting
confidence: 82%
See 1 more Smart Citation
“…As identified by previous studies [30][31][32][33][34][35], we recover evidence of strong mutational biases across the SARS-CoV-2 genome. A remarkably high proportion of CàU changes was observed relative to other types of SNPs and this pattern was observed at both non-homoplasic and homoplasic sites ( Figures S6-S8).…”
Section: Distribution Of Recurrent Mutationssupporting
confidence: 82%
“…Notably 66% of the detected mutations comprise nonsynonymous changes of which 38% derive from CàU transitions. This high compositional bias, as also detected in other studies [33][34][35], as well as in other members of the Coronaviridae [30][31][32], suggests that mutations observed in the SARS-CoV-2 genome are not solely the result of errors by the viral RNA polymerase during virus replication [33,34]. One possibility is the action of human RNA editing systems which have been implicated in innate and adaptive immunity.…”
Section: Discussionsupporting
confidence: 62%
“…There are at least four possible sources of (real or apparent) mutations that recur within independent lineages in a tree, and each makes distinct predictions about the source of recurrent mutations (Table 1). In particular, recent work has shown a strong bias towards C>U mutation in the SARS-CoV-2 genome [21,[42][43][44] . Systematic errors, which usually result from consistent errors in molecular biology techniques or bioinformatic data data processing, need not reflect this bias and are not subject to natural selection.…”
Section: Systematic Error Could Be Mistaken For Recurrent Mutation Ormentioning
confidence: 99%
“…Hypermutation rather than positive selection may explain many remaining highly recurrent sites. Previous analyses showed that the rate of C>U mutation is exceptionally high relative to other mutation types in the viral genome [10,25,43,47] . This class of mutations should show increased evidence of recurring multiple times because they experience elevated mutation rates [25] .…”
Section: Recurrent Mutations Not Associated With a Lab Reflect The Mumentioning
confidence: 99%
See 1 more Smart Citation